A comparative study to analyse the potential of 99mTc-PEI-MP for diagnosis and 188Re-PEI-MP for therapy of bladder carcinoma and osteosarcoma - Ferreira, Sara (2012)
Introduction: The water-soluble polymer PEI-MP (polyethyleneimine, functionalised with methylphosphonate groups) that might be labeled with 188Re (emits high energy B- particles) and 99mTc presents a strong potential for metabolic radiotherapy and diagnosis, respectively. The aim of this study was to evaluate in vivo the potential of 188Re-PEI-MP as therapeutic agent and 99mTc-PEI-MP asdiagnostic agent for bladder carcinoma and osteosarcoma. Material and methods: Cytotoxicity of PEI-MP was investigated in bladder carcinoma cell line (CRL-1472) using the MTT test for different concentrations of PEI-MP (1 uM to 1000 uM) and incubation times (24h, 48h, 72h and 96h).